What Do Reference Librarians Do Now? - McAdoo, Monty L. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The primary purpose of this study was to better understand the nature of “reference” and reference transactions.Methods – This study looked at four years’ of reference transaction (RT) data recorded at a small, state-owned university.Results – The data clearly indicates that the overall number of RT continues to decline. It also reveals that, despite the use of student mentors, librarians are still involved with a majority of RT, regardless of whether or not they require the expertise of a librarian to resolve.Conclusion – Continuing to be involved with RT which do not require the knowledge or training of a librarian (e.g., directional) can have a diminutive effect on the perceived role, work, and value of librarians. As such, it is suggested that these sorts of questions be addressed by student mentors or staff members. In turn, this will allow librarians to focus on those questions and activities which do require their unique knowledge and skills. Along similar lines, it is also suggested that librarians explore and identify new, non-traditional ways of applying their expertise to student success initiatives and the overall academic life of the institution. With the merger of three libraries, data from this study has been and continues to be used to make informed decisions about the provision of reference services in a new, integrated library environment.